Potential inhibitors of α-glucosidase and α-amylase enzymes from locally available fruit wastes by solid state fermentation - Ahmad Barkat, Anumsima; Jamal, Parveen; Azmi, Azlin Suhaida; Noor Batcha, Ibrahim Ali; Idris, Zulkarnain Mohamed; Arbain, Dachyar (IIUM Press,International Islamic University Malaysia, 2019)
A therapeutic approach for treating diabetes is to decrease thepost-prandial hyperglycaemia. This is done by retarding the absorption of glucose through the inhibition of carbohydrate hydrolyzing enzymes, α-amylase and α-glucosidase, in the digestive tract. Inhibition of both enzymes helps to reduce the glucose level in the blood of a diabetic patient. This study was aimed to investigate the production of α-glucosidase and α-amylase inhibitors from local fruit wastes (honeydew skin, banana peel, and pineapple skin) using solid state fermentation. Each of the fruit wastes was fermented with three different types of white rot fungus Phenarochaete chrysosporium (PC), Panus tigrinus M609RQY (M6) and RO209RQY (RO2) for 7 days. Sampling was carried out starting from day 4 to day 7 to determine the enzyme inhibition activity. The samples were extracted using water prior to enzyme analysis. Most of the fruit samples showed varying degree of percentage inhibition activity depending on the sampling time. Extract of fermented banana peels with RO2 on day 4 showed the higher α-glucosidase inhibition (56.57 ± 0.32 %), followed by honeydew extract fermented with the same fungus on the same day (39.68 ± 0.05 %). Extracts of each fruit waste sample fermented with PC showed the least α-glucosidase inhibition (below 15 %). Meanwhile for α-amylase inhibition activity, the extract from fermented honeydew skins with PC on day 7 showed the highest inhibition activity i.e. 98.29 ± 0.63%. The least inhibition activity (43.37 ± 0.54 %) was observed in the extract from honeydew skins fermented with M6 on day 5. All positive results showed that fruit wastes could be the alternative sources for antidiabetic agent especially for α-amylase and α-glucosidase inhibitors.